Alternative Approaches to Addressing the Risk of Non-Permanence in Afforestation and Reforestation Projects under the Clean Development Mechanism - Murray, Brian C.; Galik, Christopher S.; Mitchell, Stephen; Cottle, Phil (World Bank, Washington, DC, 2017)
The report provides quantitative and qualitative insights into the performance of different non-permanence approaches for consideration of parties. This note summarizes the results of the analysis presented in the report. Besides the existing mechanism for temporary crediting, the study analyzed a range of alternative approaches to addressing non-permanence, including those considered in prior deliberations of the United Nations Framework Convention on Climate Change (UNFCCC). The approaches address the risk of non-permanence in several ways. Under the tonne year accounting, credits are issued for the increments of carbon sequestered corresponding to a defined permanence period, and their quantity depends on the carbon stored in biomass each year of the permanence period. However, this approach has not been implemented by any standard. These approaches are not mutually exclusive, but can be used in tandem with each other.